PELATIHAN PENINGKATAN KEMAMPUAN PENGURUS ASOSIASI PETANI KARET KUANTAN SINGINGI (APKARKUSI) DALAM DIGITALISASI PEMASARAN KARET - Rosnita, Rosnita; Yulida, Roza; Andriani, Yulia; Septya, Fanny; Herlon, Meki (JP2N : Jurnal Pengembangan Dan Pengabdian Nusantara, 2023)
Riau Province is the third largest rubber producer in Indonesia in 2021. Kuantan Singingi Regency has the largest rubber area in Riau with an area of 126,240 Ha and production of 82,375 tons (BPS Riau Province, 2022). This district usually has the highest rubber price compared to other districts, because farmers in this district who are members of farmer groups market rubber with an auction system through the Kuantan Singingi Rubber Farmers Association (APKARKUSI). This institution fosters farmers who are members of farmer groups spread across 6 (six) sub-districts. This Community Service activity carried out at APKARKUSI in the form of Capacity Building Training for the Management of the Kuantan Singingi Rubber Farmers Association (APKARKUSI) in Digitalizing Rubber Marketing. The target of this PKM activity is members of APKARKUSI Kuantan Singingi Regency.